The Effect of Motivational Factors and Incentives on Participation and Productivity with the Mediating Role Performance - Abbasi, Mohammad Hamid; Amel, Hamid Reza; Tolarod, Mohammad Mortezei (Archives of Business Research, 2025)
In the modern organizational age, enhancing employee participation and productivity—particularly in the public sector—is a priority agenda for human resource management. This study investigates the impact of motivation and incentives on employee participation and productivity, with the moderating role of employee performance in Shiraz County government offices. The study is applied in nature and descriptive survey in method. The statistical population consisted of all the employees working in governmental agencies in Shiraz, 210 of whom were chosen randomly by simple random sampling. A standardized questionnaire was used for collecting the data, the content validity of which had been confirmed by experts and reliability calculated by Cronbach's alpha coefficient, being above 0.7. Analysis of data using the Partial Least Squares (PLS) program revealed that incentives and motivation directly and indirectly influence participation and productivity through the performance of employees. Employee performance was found to enhance the positive impact of incentives and motivation on organizational performance. The findings imply that managers can use them to develop strategies to improve performance and increase productivity in public sector organizations.